Magnetic graphene sol–gel hybrid as clean-up adsorbent for acrylamide analysis in food samples prior to GC–MS. (15th January 2018) - Rashidi Nodeh, Hamid; Wan Ibrahim, Wan Aini; Kamboh, Muhammad Afzal; Sanagi, Mohd Marsin
Highlights: Fe3 O4 @G-TEOS-MTMOS as clean-up adsorbent for direct GC–MS acrylamide analysis. The proposed method allows efficient clean-up without derivatization. The developed method achieved low limits of detection (0.061–2.89 µg kg −1 ). The proposed method provided high recoveries (82.7–105.2%) in real food samples. Fe3 O4 @G-TEOS-MTMOS RP-MSPE method has the advantages of rapidity and reliability. Abstract: Graphene (G) modified with magnetite (Fe3 O4 ) and sol–gel hybrid tetraethoxysilane-methyltrimethoxysilane (TEOS-MTMOS) was used as a clean-up adsorbent in magnetic solid phase extraction (MSPE) for direct determination of acrylamide in various food samples prior to gas chromatography-mass spectrometry analysis. Good linearity ( R 2  = 0.9990) was achieved for all samples using matrix-matched calibration. The limit of detection (LOD = 3 ×  SD/m ) obtained was 0.061–2.89 µg kg −1 for the studied food samples. Native acrylamide was found to be highest in fried potato with bright-fleshed (900.81 µg kg −1 ) and lowest in toasted bread (5.02 µg kg −1 ). High acrylamide relative recovery (RR = 82.7–105.2%) of acrylamide was obtained for spiked (5 and 50 µg kg −1 ) food samples. The Fe3 O4 @G-TEOS-MTMOS is reusable up to 7 times as a clean-up adsorbent with good recovery (>85%). The presence of native acrylamide was confirmed by mass analysis at m / z  = 71 ([C3 H5 NO] + ) and m / z  = 55 ([C3 H3 O] + ).